Charting resilience: a typology of food self-sufficiency in OECD nations - Sagit Barel-Shaked; Erez Buda (Agriculture & Food Security)
Abstract In the face of global transformations, a nation's food self-sufficiency emerges as a vital determinant of food security and resilience, driving agri-food policies. This study focuses on OECD countries and aims to analyze their food self-sufficiency ratios (SSR) in relation to economic growth and external dependencies. Utilizing data from the Food and Agriculture Organization (FAO) spanning the period 2010 to 2021, the study examines disparities across OECD nations in their perceptions and levels of food self-sufficiency. A stratified sampling procedure was employed, ensuring representation across various economic development levels. The sample size consists of all 38 OECD countries, classified into six typologies based on SSR and GDP per capita. The study employs statistical analyses, including mean comparisons and T tests, to assess variations between the different typologies of countries and their food self-sufficiency across key food categories. The findings indicate that affluent European countries tend to have low SSRs despite high economic growth, relying heavily on food imports. Conversely, less prosperous nations exhibit higher self-sufficiency, emphasizing local food production as a resilience strategy. By incorporating a classification approach, this research provides a detailed insight into food security dynamics beyond aggregate measures. A key strength of the study lies in its ability to offer a comprehensive typology of food self-sufficiency in developed nations, allowing policymakers to pinpoint areas where reliance on external food sources is particularly high. In addition, the focus on food categories rather than broad national SSR averages provides a more nuanced understanding of self-sufficiency trends. However, a notable limitation is the exclusion of more recent global disruptions beyond COVID-19 due to the data availability constraints, which may impact long-term projections. Moreover, reliance on FAO statistics may not fully capture informal or subsistence agricultural contributions. This study underscores the importance of understanding economic dynamics and agricultural policy reforms to address complexities in achieving food self-sufficiency. The findings provide valuable insights for policymakers seeking to enhance national resilience and reduce vulnerabilities in global food markets.